2013
DOI: 10.11622/smedj.2013242
|View full text |Cite
|
Sign up to set email alerts
|

Total laparoscopic Wertheim’s radical hysterectomy versus Wertheim’s radical abdominal hysterectomy in the management of stage I cervical cancer in Singapore: a pilot study

Abstract: METHODSThis was a prospective pilot study comparing TLRH with RAH in a single large tertiary institution in Singapore. Inclusion criteria included surgically fit patients with early cervical cancer and no radiological evidence of regional or distant metastases. RESUlTSFrom November 2009 to February 2011, a total of 18 TLRHs and 30 RAHs were performed. The median blood loss in the TLRH group was significantly lower than that in the RAH group (300 mL vs. 500 mL; p = 0.04). However, there was no statistically sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 20 publications
0
19
0
5
Order By: Relevance
“…The number of dissected lymph nodes reported in eight studies (Table 3 ) [ 20 23 , 25 , 27 , 28 , 30 , 31 ] showed comparable difference in both techniques (weighted mean difference = −1.06; 95 % CI −4.03 to 1.91; p = 0.48; Fig. 3 ).…”
Section: Resultsmentioning
confidence: 98%
“…The number of dissected lymph nodes reported in eight studies (Table 3 ) [ 20 23 , 25 , 27 , 28 , 30 , 31 ] showed comparable difference in both techniques (weighted mean difference = −1.06; 95 % CI −4.03 to 1.91; p = 0.48; Fig. 3 ).…”
Section: Resultsmentioning
confidence: 98%
“…Table 1 shows the characteristics of included studies, which included 1 small RCT 15 (Level of Evidence 2b), 15 retrospective studies, 16–29 , 37 and 6 prospective studies 30–33 , 35 , 36 comparing a contemporary series of patients (Level of Evidence 3b). Five studies examined cases with Stage IB1 or below disease.…”
Section: Resultsmentioning
confidence: 99%
“…Egy 2015-ös metaanalízis, ami 12 klinikai vizsgálat eredményeit összegezi, a TRLH-t megfelelő technikának tartja a cervixcarcinoma műtéti ellátására, jobb rövid távú kimenetellel, mint az ARH [16] [17][18][19][20][21]. Malzoni és mtsai szerint a laparoszkópos csoportban szignifikánsan alacsonyabb intraoperatív vérveszteség és hospitalizáció, valamint hosszabb műtéti idő volt az ARH-csoporthoz képest.…”
Section: Megbeszélésunclassified
“…Sem a progreszsziómentes túlélésben, sem a teljes túlélésben nem volt különbség a két csoport között az ötéves nyomon követés során [19]. Lim és mtsai közleményében is kevesebbnek adódott az intraoperatív vérveszteség TLRH során, mint ARH kapcsán, de nem volt eltérés a műtéti időben, a vérvesztésben, a hospitalizációban, az eltávolított nyirokcsomók számában, valamint az intra-és posztoperatív komplikációk gyakoriságában [20]. Xiao és mtsai eredményeiben a TLRH-csoportban kevesebb volt a vérveszteség és a posztoperatív komplikáció, továbbá az ARHcsoportban több nyirokcsomót távolítottak el.…”
Section: Megbeszélésunclassified